2021
DOI: 10.3389/fcimb.2021.730413
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Host Glycolysis as a Strategy for Antimalarial Development

Abstract: Glycolysis controls cellular energy, redox balance, and biosynthesis. Antiglycolytic therapies are under investigation for treatment of obesity, cancer, aging, autoimmunity, and microbial diseases. Interrupting glycolysis is highly valued as a therapeutic strategy, because glycolytic disruption is generally tolerated in mammals. Unfortunately, anemia is a known dose-limiting side effect of these inhibitors and presents a major caveat to development of antiglycolytic therapies. We developed specific inhibitors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 76 publications
(92 reference statements)
1
14
0
Order By: Relevance
“…Targeting host glycolysis as an antimalarial strategy is a promising approach and has been attempted in a few studies. Jezewski et al (2021) observed that enolase inhibition increased erythrocyte susceptibility to oxidative damage and induces rapid and premature erythrocyte senescence, rather than direct hemolysis, also affecting parasite development. However, an inhibitory effect also on parasite enolase was not unequivocally ruled out, so the interaction mechanism was not clearly established.…”
Section: Discussionmentioning
confidence: 98%
“…Targeting host glycolysis as an antimalarial strategy is a promising approach and has been attempted in a few studies. Jezewski et al (2021) observed that enolase inhibition increased erythrocyte susceptibility to oxidative damage and induces rapid and premature erythrocyte senescence, rather than direct hemolysis, also affecting parasite development. However, an inhibitory effect also on parasite enolase was not unequivocally ruled out, so the interaction mechanism was not clearly established.…”
Section: Discussionmentioning
confidence: 98%
“…1 H NMR (600 MHz, CDCl 3 ) 8.24 (s, 1H), 5.77 (q, J = 7.8, 5.4, 5.4 Hz, 2H), 5.73 (t, J = 6.7, 7.7 Hz, 2H), 4.94 (m, 2H), 3.65 (m, 2H), 3.17 (dt, J = 27.9 Hz, 1H), 2.25 (m, 1H), 2.15 (m, 2H), 1.92 (m, 1H), 1.31−1.34 (m, 12H). 13…”
Section: ((1-hydroxy-2-oxopiperidin-3-yl)phosphoryl)bis(oxy))bis-(met...mentioning
confidence: 99%
“…1 H NMR (500 MHz, CDCl 3 ): δ 9.85 (s, 1H), 4.06−4.27 (m, 4H), 3.31−3.43 (m, 2H), 3.10 (q, J = 7.01 Hz, 4H), 3.04 (dt, J = 26.35 Hz, J = 7.06 Hz, 1H), 1.79−1.90 (m, 1H), 1.70−1.76 (m, 1H), 1.62−1.69 (m, 1H), 1.51−1.58 (m, 1H), 1.17 (s, 18H). 13…”
Section: Ss′-((((1-hydroxy-2-oxopiperidin-3-yl)phosphoryl)bis-(oxy))b...mentioning
confidence: 99%
See 2 more Smart Citations